Registros microclimáticos en recintos de siembra arqueológicos de Coctaca, prov. de Jujuy, Argentina - Albeck, María Ester (2000)
The 'high wall benches' known from Coctaca are thought to change microclimatic conditions, favouring crops cultivated inside the walls. Air and soil temperature, air humidity and winds are tested inside and outside the benches. The microclimatic changes observed are evaluated as to whether they could be significant for eventual crops